Advancing emergency airway management by reducing intubation time at a high-volume academic emergency department. (3rd August 2021) - Gopinath, Bharath; Sachdeva, Seema; Kumar, Akshay; Kumar, Gaurav
Abstract : Background: Airway management is a life-saving procedure in the emergency department (ED). Hypoxia during rapid sequence intubation (RSI) is associated with high morbidity and mortality. Aim: To decrease the median time of intubation (time from administration of paralytic agent to the successful passage of endotracheal tube) by 40% from baseline 300 s in patients undergoing RSI in the ED. Methods: A multidisciplinary quality improvement team worked to improve the airway management. The bottle necks identified using process mapping and fish bone analysis were lack of formal training of residents and nursing officers, and communication gap between residents and nursing officers. Change ideas focused on training residents in laryngoscopy and intubation and nursing officers in facilitating airway management by preparation of drugs and equipment; on-site awareness of logistical issues to the residents and nursing officers, introducing airway drug checklist and ensuring availability of difficult airway equipment. Results: After implementation of change ideas there was a significant reduction in intubation time. At the end of first Plan-Do-Study-Act (PDSA) cycle median intubation time was 165 s (IQR 125 s). By the end of last PDSA cycle, median intubation time reduced to 157 s (IQR 66 s). A shift was obtained on the run chart with a new median time of 141.5 s from mid-PDSA 1. The 8-week data after the end of PDSA 3 showed sustainability with median time of 126 s (IQR 42 s). Conclusion: A well organised team effort, simple change ideas such as structured training of residents and nursing officers, introduction of airway drug checklist and improved communication can decrease the intubation time in a chaotic ED.